ANALISIS PEMBANGUNAN SEKTOR PERTANIAN BERPERSPEKTIF GENDER DI KABUPATEN NGAWI - Rokhani Rokhani (University of Jember, 2009)
The aims of the research were (1) to understanding the role of husband and its wife in farm management, (2) to study the time allocation both husband and its wife in farm management, and(3) to study factor that influence time allocation both husband and its wife in farm management. The research location was decided by purposive method in Klitik, Geneng, Ngawi, East Java. So the 30 samples were decided by random sampling method. Furthermore, the analyze methods that used are independent t-test and multiple regression analyze.The results show that the husband participations greater than wife participation in farm management. So, the factors that influencing husband in farm management are harvested area and the age of farmer. Furthermore, the factor that influencing wife in farm management is harvested area. So, another result show that husband has main role than wife for controlling the raw material using. In contrary, wife has main role to use the harvested results. Factors that influence the time allocation in farm management are harvested area and time allocation in non farming, so the factors that influencing wife in farm management are harvested area, farm income, time allocation in non farm management.Keywords: gender model development, time allocation for farming and non farming.